Analysis of Interactive Marketing Communication Development Based on Social Media in an Indonesian Telecommunications Company - Praratya, Atalia; Narimawati, Umi; Indriani, Dewi (KnE Social Sciences, 2024)
TELKOM Tamalanrea Automated Telephone Center (ATC) is one of the automated telephone centers that supports telecommunication activities in Makassar city. ATC TELKOM has a strategy in marketing Indihome products, namely by a door-to-door and open table. For digital marketing, TELKOM’s ATC only utilizes the Search Engine Optimization (SEO) system owned by TELKOM Indonesia to market products, however, interactive marketing using social media has not been able to drive sales of Indihome products and other services. This study aimed to determine the promotional design that was carried out and to develop interactive content on social media to support the marketing and sales of Indihome products at TELKOM Tamalanrea. This study uses a qualitative descriptive analysis technique, namely, to describe the data that has been collected descriptively through interviews, observation, and field research. In carrying out the research, development, and implementation stages of interactive content on WhatsApp social media, the author manages WhatsApp accounts and develops interactive promotional content using several WhatsApp features. The results of the development and implementation of interactive content on WhatsApp social media carried out by the author during the research were effective. Keywords: interactive content, WhatsApp, social media marketing